Effectiveness of early glucocorticoids in myasthenia gravis: a retrospective cohort study - Zhen, Lulu; Zhao, Xue; Li, Wenbo; Wu, Jinru; Shang, Haodong; Chen, Shufan; Zhu, Xiaoyan; Wang, Yiren; Yu, Xiaoxiao; Hu, Guanlian; Sun, Zhan; Zhang, Yingna; et al. (Frontiers in Neurology, 2023)
Purpose This study aimed to clarify the effect of early glucocorticoid (GC) application on achieving minimal manifestation (MM) status or better in the treatment of myasthenia gravis (MG) in the early clinical phase. Methods A retrospective analysis was performed using data from 336 patients with MG who received GC therapy from January 2015 to September 2022 in the Zhengzhou University Henan Institute of Medical and Pharmaceutical Sciences Myasthenia Gravis Biobank (ZMB). Patients were divided into two groups: the early mono-GC group (treated with GC within 6 months of MG onset) and the delayed mono-GC group. Results Kaplan–Meier analysis showed that the early mono-GC group achieved MM status earlier and more frequently than the delayed mono-GC group (log-rank test, p = 0.0082; hazard ratio [HR], 1.66; p = 0.011). The early mono-GC group had a lower maintenance oral GC dose than the delayed mono-GC group. In multivariate Cox regression analysis, early mono-GC (HR, 1.50; p = 0.043), early-onset MG (EOMG) (HR, 1.74; p = 0.034), and ocular MG (OMG) (HR, 1.90; p = 0.007) were associated with MM status or better. In conclusion, early mono-GC, EOMG, and OMG were positive predictors of treatment goals. In EOMG, OMG, and acetylcholine receptor antibody-positive MG (AChR-MG) subgroups, the maintenance oral GC doses in the early mono-GC group were significantly lower than the doses in the delayed mono-GC group (p < 0.05). Conclusion Early intervention with GC led to better long-term outcomes and reduced the necessary maintenance dose of oral GC for patients with MG. EOMG and OMG were positive predictors of MM status or better with mono-GC.